(untitled) - McCracken, Daniel D. (New York, 1988)
This book is also available through the Introductory Engineering Custom Publishing System. If you are interested in creating a course-pack that includes chapters from this book, you can get further information by calling 212-850-6272 or sending email inquiries to engineer&atsign;jwiley.com. A complete treatment of the American National Standard FORTRAN 77 language, this book also offers good coverage of debugging. Promotes clear programming style and easily maintainable programs, via top-down, modular design techniques. Examples are representative of those written on interactive terminals, and many of the runs are illustrated as they appear on MS-DOS machines and Macintoshes. The examples provided (over 135, in all) are highly transportable--all programs have been tested on several systems. Flexible enough for one-quarter to two-semester courses.
Keywords: Engineering,Kỹ thuật; Data processing,Xử lý dữ liệu